Cloud Computing for Large-Scale Resource Computation and Storage in Machine Learning - Wang, Yufu; Bao, Qiaozhi; Wang, Jiufan; Su, Guangze; Xu, Xiaonan (Journal of Theory and Practice of Engineering Science, 2024)
With the rapid development of Internet technology, cloud computing technology has gradually entered people's lives. Cloud computing provides users with various IT resources (computing, storage, etc.) in data centers all over the world through the Internet. Currently, there are hundreds of thousands of servers in large-scale data centers, and effective management of resources in such large-scale data centers is a major problem in academia and industry. This article explores the importance and pervasive use of cloud computing and machine learning in today's technology landscape. As the global cloud computing market size and the application of machine learning technologies continue to grow, the demand for computing and storage resources is also increasing. This paper aims to solve the challenges of large-scale resource computing and storage requirements in machine learning, and puts forward a solution how to give full play to the advantages of cloud computing platform and combine machine learning algorithms and technologies. Through practical data and case studies, we highlight the application scenarios, advantages and challenges of cloud computing in machine learning, and look forward to the future development trend.